Remyelination in animal models of multiple sclerosis: finding the elusive grail of regeneration - Packer, Davin; Fresenko, Emily E.; Harrington, Em P. (Frontiers in Molecular Neuroscience, 2023)
Remyelination biology and the therapeutic potential of restoring myelin sheaths to prevent neurodegeneration and disability in multiple sclerosis (MS) has made considerable gains over the past decade with many regeneration strategies undergoing tested in MS clinical trials. Animal models used to investigate oligodendroglial responses and regeneration of myelin vary considerably in the mechanism of demyelination, involvement of inflammatory cells, neurodegeneration and capacity for remyelination. The investigation of remyelination in the context of aging and an inflammatory environment are of considerable interest for the potential translation to progressive multiple sclerosis. Here we review how remyelination is assessed in mouse models of demyelination, differences and advantages of these models, therapeutic strategies that have emerged and current pro-remyelination clinical trials.